Secondary Flow Phenomenon at Elbow Ducting of The Closed-Circuit Subsonic Wind Tunnel: An Experimental Study - A K Faizin; Sutardi; L Edahwati; W D Lestari; N Adyono; R D Issafira; W Saputro; T P Sari (BIOMEJ, 2022)
The installation of elbow ducting in closed-loop wind tunnel installation will cause a pressure drop. Pressure drop was caused by flow separation and secondary flow phenomenon in the elbow ducting. The test section used in this experimental study was an octagonal elbow 90º with radius ratio (rm/Dh) = 0.6. Diameter hydraulic (Dh) elbow of 806 mm. In this study, the Reynolds number is measured based on the free flow velocity (U∞) inlet section, that is ReDh = 4.63x105. The experimental results showed the pressure drop is ΔCp = 1.46 for Re = 4.63x105. This difference in pressure value between the outer and inner (ΔCp) of the elbow ducting was caused by secondary flow. The secondary flow was observed through a horizontal velocity profile where at xi/Dh = 1.35, fluid flow was accelerated on the inner wall and decelerated on the outer wall of the ducting elbow. Then, at xi/Dh = 1.63 to xi/Dh = 2.01, there are gradual shifts of the velocity profile where the fluid flow is accelerated toward the outer wall.